4x+12=3(x+4)

Simple and best practice solution for 4x+12=3(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+12=3(x+4) equation:


Simplifying
4x + 12 = 3(x + 4)

Reorder the terms:
12 + 4x = 3(x + 4)

Reorder the terms:
12 + 4x = 3(4 + x)
12 + 4x = (4 * 3 + x * 3)
12 + 4x = (12 + 3x)

Add '-12' to each side of the equation.
12 + -12 + 4x = 12 + -12 + 3x

Combine like terms: 12 + -12 = 0
0 + 4x = 12 + -12 + 3x
4x = 12 + -12 + 3x

Combine like terms: 12 + -12 = 0
4x = 0 + 3x
4x = 3x

Solving
4x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
4x + -3x = 3x + -3x

Combine like terms: 4x + -3x = 1x
1x = 3x + -3x

Combine like terms: 3x + -3x = 0
1x = 0

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| -56=-4x-2(-7x-2) | | 7(6+x)=6(2-x) | | 328=8(6a+5) | | -5x=-x-12 | | 10x^2-66x+72=0 | | -4x+83=-12x-125 | | 0.5y-2=-.25 | | 10+5(x-2)=4x+1 | | -29=5x-2(3x+10) | | 36x+24=10(x+2+2x) | | 7h-14=42 | | -4-3=0.4x-2y | | -4(x+4)=2(x-10) | | 5g+15=42 | | 314=-x+576 | | -4-3=0.4-2y | | 2(4x+6)=-13+1 | | 3(3z-1)-3(3-2Z)=12 | | x+1=-x+3 | | 19+2(2n-15)=1 | | -4=-3x+5(-x+12) | | Ln(x-4)+ln(x-1)=ln(x-8) | | lnx=-10 | | 2[x+5(6-x)+18]-10=50-10x | | 28=t+24 | | -8(-8+2p)=192 | | 3x-x+6x=17 | | 12c-4=-12c | | 12-5x=6(x+2) | | 3.4k=7.82 | | 2q-5=11 | | 225x^2-121y^2= |

Equations solver categories